Altered multisensory integration in pilots: Examining susceptibility to fission and fusion sound-induced flash illusions - Xing Peng; Yaowei Liang; Xiuyi Li; Jiaying Sun; Xiaoyu Tang; Aijun Wang; Chengyi Zeng (i-Perception)
Pilots show superior visual processing capabilities in many visual domain tasks. However, the extent to which this perceptual advantage extends to multisensory processing requires validation. In this study, we examined multisensory integration of auditory and visual information in both pilot and control groups, utilizing two sound-induced flash illusions (SIFI) tasks: the fission illusion, where one flash coupled with two beeps is perceived as two flashes; and the fusion illusion, where two flashes with a single beep are perceived as one flash. Sixty-six participants were instructed to discern whether they observed one or two flashes while discounting irrelevant auditory beeps, across six conditions: one flash (1F), two flashes (2F), one flash/one beep (1F1B), one flash/two beeps (1F2B), two flashes/one beep (2F1B), and two flashes/two beeps (2F2B). We varied six stimulus onset asynchronies (SOAs) between auditory and visual events (25–150 ms) to assess the participants’ temporal binding window (TBW). Signal detection theory was employed to analyze the group differences in illusion reports. The findings suggest that, while pilots are less susceptible to SIFI in either fission or fusion conditions, they only exhibit narrower TBW in the fusion condition, where pilots demonstrated a more gradual change in their susceptibility as SOA increases. In the fission condition, the group difference was primarily driven by visual sensitivity, whereas in the fusion condition it also likely reflected pilots’ distinct multisensory integration mechanisms. Two alternative possibilities are discussed to explain the group differences and the different multisensory integration patterns in fission and fusion conditions.